Adrenal masses in children: Imaging, surgical treatment and outcome - Şenol Emre; Rahşan Özcan; Ayten Ceren Bakır; Sebuh Kuruğoğlu; Nil Çomunoğlu; Hilal Susam Şen; Tiraje Celkan; Gonca Topuzlu Tekant (Asian Journal of Surgery, 2020)
Background/objective: This study aims to evaluate the current surgical approach to adrenal masses in the pediatric age group. Methods: We retrospectively analyzed cases that underwent surgery for adrenal masses between 2007 and 2017. Patients were assessed regarding age, sex, primary diagnosis, image defined risk factors (IDRF), surgical treatment method, complications, duration of hospital stay, and follow-up. Results: We examined 50 patients who underwent surgery for adrenal mass (mean age: 4.8 years; range: 5 days–14 years). For IDRF assessment, Ultrasonography was used in 42, Computed Tomography in 36, and Magnetic Resonance Imaging in 36 patients. Lesions were present on the right in 25, left in 21, and bilateral in 4 patients. Histopathological findings were neuroblastoma (n = 29), ganglioneuroma (n = 6), adrenal cortex tumor (n = 5), ganglioneuroblastoma (n = 4), pheochromocytoma (n = 3), cyst (n = 1), and adrenal hematoma (n = 2). Laparotomy was performed on 37 patients, and laparoscopy on 13 patients. None of the cases had any operative complications. Conclusion: The crucial factors determining the surgical approach to adrenal masses in pediatric cases are the histopathology of the mass, volume, and IDRF. Minimally invasive procedures could be reliably performed in appropriate cases. Keywords: Adrenal mass, Image defined risk factors, Adrenal cysts, Neuroblastoma, Pheochromocytoma